2012 Presidential Elections on Twitter -- An Analysis of How the US and French Election were Reflected in Tweets - Nooralahzadeh, Farhad; Arunachalam, Viswanathan; Chiru, Costin (2013 19th International Conference on Control Systems and Computer Science, 2013)
The main objective of this paper is to compare the sentiments that prevailed before and after the presidential elections, held in both US and France in the year 2012. To achieve this objective we extracted the content information from a social medium such as Twitter and used the tweets from electoral candidates and the public users (voters), collected by means of crawling during the course of election. In order to gain useful insights about the US elections, we scored the sentiments for each tweet using different metrics and performed a time series analysis for candidates and different topics (identified by specific keywords). In addition to this, we compared some of our insights obtained from the US election with what we have observed for the French election. This deep dive analysis was done in order to understand the inherent nature of elections and to bring out the influence of social media on elections.